HUBUNGAN PERISTIWA ISRAK MIKRAJ DENGAN TEOR RELATIVITAS EINSTEIN - Hilda, Lelya (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2014)
Albert Einstein was a German-born theoretical physicist who developed the  theory of relativity.  The theory of relativity was representative of more than a single new physical theory. There are some explanations for this. First, special relativity was published in 1905, and the final form of  general relativity was published in 1916.   The  theory  of relativity  has proved  the truth of  the events  Israk   Mikraj  ascension. Israk  Mikraj  is not a  metaphysical  event.  He  is a  physical  event  (real;  physical) experienced and  lived  the Prophet Muhammad with his consciousness.   The event of Israk and Mikraj are referred to briefly in the Qur'an. Within the Qur'an itself,  there are two verses in chapter 17, which has been named after the Isra, and is called Surah Al-Isra. There is also some information in Surah  An-Najm, which some scholars say is related to the Israk and Mikraj